Implementing and continuity of lean construction using discrete event simulation - Shahin Dabirian (Iranian Society of Structrual Engineering (ISSE), 2019)
The success of lean principles in manufacturing and the benefits arising from its use is one of the main motivations for adopting lean principles in construction .The lean construction strives for the same goals as lean production, namely to eliminate waste and to maximize value. One of the basic concepts in lean construction is called “perfection”, meaning that efforts made to decrease waste in every single phase of the projects has no limit and the enhancements resulted from implementation of lean principles must always be retained and improved. This paper pays attention to application of lean thinking in one of construction fields as a case study. Another aim could be mentioned as continuity of resulted enhancements caused by application of the theory by following perfection principle. To achieve and investigate the results, discrete event simulation for making activity under-study cycle model has been used. The case study in this research is foam concrete process in execution phase. The required data for building the simulation model has been collected using work and time study technique. Primary results show that different kinds of waste in a construction process can be reduced via adopting lean construction principles using computer simulation. The results obtained from applying lean principles demonstrate enhancement in performance of foam concrete cycle up to 15% and decrease in time up to 36%.